Large-scale micropropagation of the Australian key species Gahnia radula (Cyperaceae) and its return to revegetation sites - Kodym, A.; Clarke, I.; Aponte, C.; Turner, Shane; Bunn, E.; Delpratt, J. (2014)
We report on the successful propagation of the sedge Gahnia radula (R.Br.) Benth. from seed by using plant tissue culture, and its successful establishment in the field. This keystone species, although common along parts of the eastern coast of Australia, is currently not available for revegetation because of a lack of efficient propagation methods, leading to the use of substitute species in many restoration programs. Even though seed quality is a common problem for G. radula, one population bearing filled seed was located in the near-east of Melbourne and after harvest of fruit in December 2011, seeds were successfully germinated in vitro after removal of the pericarp. Overnight soaking in sterile 10% (v/v) smoke water before culturing enhanced in vitro germination from 29.2% to 66.7%. In vitro-grown seedlings were then used as starting material for tissue-culture propagation via shoot culture. A micropropagation rate of about six new plantlets per cycle was achieved within 5-6 weeks with liquid half-strength Murashige-Skoog medium and a pulse treatment with 10 M 6-benzylaminopurine (BAP) and 2 M naphthalene acetic acid (NAA). Plants rooted after receiving a pulse treatment with 5 M kinetin and were successfully acclimatised into potting mix and were ready for field planting after 5-6 months. Tube stock was planted into two field sites with minimal weed control. Survival was 98% in both cases 1 month after planting and 54% and 74% after the summer. Division of in vitro-derived plants in the nursery was very successful, with 93-96% establishment of divisions. This research highlights the important role of plant tissue culture in conserving biodiversity of native flora.